Perspective from Africa - Mangheni, Margaret Najjingo (2020)
Margaret Najjingo Mangheni BOOK LAUNCH Virtual Event - Agricultural Extension: Global Status and Performance in Selected Countries Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) SEP 10, 2020 - 09:30 AM TO 11:00 AM EDT